The integration of ERP systems and technologies for process automation: an analysis of the literature - Maldareanu, Andreea; Dumitru, Valentin Florentin (Transformations In Business & Economics, 2025)
In the context of Industry 4.0, economic entities that want to be successful on the market have to take into consideration the use of various technologies for digitalisation and automation of operational processes. To facilitate work and increase performance, ERP (Enterprise Resource Planning) systems can be integrated with other innovative solutions for automation, such as RPA (Robotic Process Automation). This paper aims to identify the main topics of interest in the field and the correlations between them by using a bibliometric literature analysis. The database included 284 publications extracted from Scopus. The search was carried out using keywords such as ‘ERP’, ‘RPA’, and ‘automation’. Using the VOSviewer software, the answers to the research questions were obtained by analysing keyword co-occurrence network, the evolution of the number of papers published in the period 2015–2024, the papers with the highest number of citations, the representative authors, the sources that include the largest number of publications, and the countries that contributed the most to the field. The results illustrate that there is an increasing interest in the integration of ERP systems with digitalisation and automation technologies. In the analysed papers, automation-based solutions, such as software robots, are mainly chosen. The current research contributes to the literature by exploring the integrated use of ERP solutions with RPA, an aspect that is not much addressed in existing work. An overview of trends takes shape as this study can represent the basis for future research in this particular, continuously evolving field.
Keywords: ERP – Enterprise Resource Planning; RPA – Robotic Process Automation; economic processes; process automation technologies; literature review